Impact of Paraspinal Sarcopenia on Clinical Outcomes in Intervertebral Disc Degeneration Patients Following Percutaneous Transforaminal Endoscopic Lumbar Discectomy - Tianci Fang; Zhifang Xue; Quan Zhou; Jiawen Gao; Jian Mi; Huilin Yang; Feng Zhou; Hao Liu; Junxin Zhang (Orthopaedic Surgery)
ABSTRACT Objective The paraspinal muscles are a crucial component of the spine's extrinsic stabilization system. While the impact of paraspinal muscle sarcopenia on patient‐reported outcome measures (PROMs) after lumbar surgery is well known, its effects following percutaneous transforaminal endoscopic discectomy (PTED) have not been investigated. To investigate the prognostic value of preoperative paraspinal sarcopenia on long‐term PROMs after PTED, and to identify independent predictors of chronic postoperative low back pain. Methods In this retrospective cohort study, 145 patients who underwent PTED for lumbar disc herniation (2017–2022) were stratified into sarcopenia (n = 52) and non‐sarcopenia (n = 93) groups using sex‐specific psoas muscle index (PMI) thresholds (male: < 6.36 cm2/m2; female: < 3.92 cm2/m2). Preoperative MRI/CT was used to quantify paraspinal muscle parameters, including PMI, multifidus muscle index (MMI), erector spinae muscle index (EMI), Goutallier‐classified fat infiltration (FI) severity (Grades 0–4), and multifidus muscle density (MMD). Primary outcomes were assessed via the visual analog scale (VAS; 0–10) and Oswestry disability index (ODI; 0%–100%) at preoperative, 1‐month, 6‐month, and final follow‐up (mean 65.6 weeks). Multivariate logistic regression was performed to identify independent predictors of chronic pain (defined as VAS ≥ 4 at final follow‐up). Results The study cohort comprised 145 patients (69 female, 76 male; mean age: 50.1 ± 7.6 years). The sarcopenia group exhibited significantly lower muscle indices (PMI: 4.55 vs. 7.48 cm2/m2, p < 0.001, MMI: 2.61 ± 0.80 vs. 3.66 ± 0.94 cm2/m2, p < 0.001, EMI: 9.72 ± 2.46 vs. 12.54 ± 2.27 cm2/m2, p < 0.001) and higher FI severity (p < 0.05). At final follow‐up, the sarcopenia group reported significantly worse pain (VAS: 3.04 ± 1.25 vs. 2.31 ± 1.50, p = 0.004) and disability (ODI: 28.33 ± 6.61 vs. 21.57 ± 7.28, p < 0.001). Multivariate analysis identified BMI (OR = 1.319), PMI (OR = 0.745), MMI (OR = 0.454), and moderate/severe multifidus FI (OR = 7.036) as independent predictors of chronic pain (all p < 0.05). Conclusion Paraspinal sarcopenia, particularly multifidus degeneration, is a modifiable determinant of chronic pain after PTED. Preoperative muscle quality assessment combined with targeted rehabilitation may optimize outcomes.